2015
DOI: 10.1128/aem.01741-15
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Risks of Multiple-Drug-Resistant Enterococcus spp. in Southeast Asia

Abstract: Enterococci rank as one of the leading causes of nosocomial infections, such as urinary tract infections, surgical wound infections, and endocarditis, in humans. These infections can be hard to treat because of the rising incidence of antibiotic resistance. Enterococci inhabiting nonhuman reservoirs appear to play a critical role in the acquisition and dissemination of antibiotic resistance determinants. The spread of antibiotic resistance has become a major concern in both human and veterinary medicine, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 50 publications
0
33
1
Order By: Relevance
“…Concern the resistance patterns, MDR, XDR and PDR, the results revealed that 1/28 Different percentage of MDR-enterococci were stated in many studies (28-63%) [47][48][49][50] . XDRenterococci were also stated in many studies and compile ( 8-35%) of isolated enterococci.…”
Section: Resultsmentioning
confidence: 99%
“…Concern the resistance patterns, MDR, XDR and PDR, the results revealed that 1/28 Different percentage of MDR-enterococci were stated in many studies (28-63%) [47][48][49][50] . XDRenterococci were also stated in many studies and compile ( 8-35%) of isolated enterococci.…”
Section: Resultsmentioning
confidence: 99%
“…They cause frequently more infections in patients hospitalized for a long time or who have received multiple antibiotic therapy [1,2]. E. faecalis and E. faecium are the most prevalent species cultured from human infections and are frequently associated with nosocomial infections worldwide [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of bacteria to adapt and become resistant to antibiotics has been recognized by the scientific community for many decades. Staphylococcus aureus, 1 Acinetobacter baumannii, 2 and Enterococci species 3 are just some of the nosocomial pathogens with increased antimicrobial resistance (AMR) that cause difficult-to-treat infections worldwide. AMR is commonly accrued through genetic changes, which confer a more resistant phenotype on the cell, or through the integration of the cell into a biofilm, which can lead to a transient increase in tolerance to antibiotics of up to 1,000-fold.…”
Section: The Problem Of Antibiotic Resistancementioning
confidence: 99%